2015
DOI: 10.1111/ijd.12841
|View full text |Cite
|
Sign up to set email alerts
|

Topical cannabinoid receptor 1 agonist attenuates the cutaneous inflammatory responses in oxazolone‐induced atopic dermatitis model

Abstract: All of the results suggest that topical application of CB1R-specific agonist can be beneficial for alleviating the inflammatory symptoms in chronic skin diseases, including atopic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 28 publications
0
31
0
1
Order By: Relevance
“…Two major CBRs are CB1 and CB2, and recently another G protein-coupled cannabinoid receptor, GPR55, has emerged as a type 3 CBR [58]. Several studies have shown that CB1 agonists relieve inflammatory symptoms [59] by downregulating mast cell activation [60] and decreasing keratinocyte-derived proinflammatory mediators [61]. In addition, CB2 agonists suppress skin inflammation by inhibiting inflammatory cell migration [62], and GPR55, which is found in mast cells, has anti-inflammatory effects by inhibiting mast cell-mediated release of nerve growth factor and reducing angiogenesis [63].…”
Section: Discussionmentioning
confidence: 99%
“…Two major CBRs are CB1 and CB2, and recently another G protein-coupled cannabinoid receptor, GPR55, has emerged as a type 3 CBR [58]. Several studies have shown that CB1 agonists relieve inflammatory symptoms [59] by downregulating mast cell activation [60] and decreasing keratinocyte-derived proinflammatory mediators [61]. In addition, CB2 agonists suppress skin inflammation by inhibiting inflammatory cell migration [62], and GPR55, which is found in mast cells, has anti-inflammatory effects by inhibiting mast cell-mediated release of nerve growth factor and reducing angiogenesis [63].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in an in vivo experimental model using phorbol ester-induced acute inflammation developed in mice and atopic dermatitis-like symptoms induced with oxazolone, CB1 agonists proved their anti-inflammatory action through several proposed mechanisms. Mast-cells downregulation, peroxisome-proliferator activated receptors (PPARs) activation, and the decrease of epidermal production of IFN-γ and several chemokines, such as CCL2, CCL8, and CXL10 were the possible anti-inflammatory involved pathways [115,116].…”
Section: Allergic Contact Dermatitismentioning
confidence: 99%
“…Mice with CB1 -/keratinocytes presented higher skin inflammation, eosinophil infiltration, and expression levels of IL-4, TSLP, and CCL8 when challenged with fluorescein isothiocyanate [138]. Topical administration of AEA and α-oleoyl oleylamine serinol (α-OOS), a synthetic CB1 agonist, accelerated barrier recovery and reduced chemokines in both oxazolone-and tetradecanoylphorbol acetate-induced AD models [140,141]. CB1 activation also showed anti-inflammatory functions, reduced mast cell recruitment, proliferation, and degranulation, and decreased Th2 cytokines [73,141,142].…”
Section: Cannabinoids In Allergy 575mentioning
confidence: 99%